1996
DOI: 10.1016/s0006-3495(96)79473-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the kinetics of DNA hybridization with gel-immobilized oligonucleotides

Abstract: A new method of DNA sequencing by hybridization using a microchip containing a set of immobilized oligonucleotides is being developed. A theoretical analysis is presented of the kinetics of DNA hybridization with deoxynucleotide molecules chemically tethered in a polyacrylamide gel layer. The analysis has shown that long-term evolution of the spatial distribution and of the amount of DNA bound in a hybridization cell is governed by "retarded diffusion," i.e., diffusion of the DNA interrupted by repeated associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 20 publications
5
94
0
Order By: Relevance
“…In this scenario, the effect of free energy penalty associated with mismatched base pairs becomes a fraction of the total free energy of binding (2). This would explain why mismatches associated in shorter sequences promote higher levels of destabilization in a duplex (3,18).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the effect of free energy penalty associated with mismatched base pairs becomes a fraction of the total free energy of binding (2). This would explain why mismatches associated in shorter sequences promote higher levels of destabilization in a duplex (3,18).…”
Section: Discussionmentioning
confidence: 99%
“…Solid surface hybridizations with linear DNA and PNA probes have been used to study association and dissociation rates. For example, using immobilized linear DNA oligonucleotide probes, Livshits and Mirzabekov demonstrated that the association rate constant was the same for target and nontarget DNA (27), and Dai et al showed that nontargets exhibited higher dissociation rate constants than targets, which resulted in faster overall kinetics for nontarget (14). In contrast, immobilized linear PNA probes generally exhibited higher association rate constants and lower dissociation rate constants for targets than for nontargets (21).…”
Section: Discussionmentioning
confidence: 99%
“…The theory of hybridization of nucleic acid to gel-immobilized oligonucleotides has been developed [Livshits and Mirzabekov, 1996]. The efficiency of the discrimination depends on the position of the mismatch within the probe, the length of the probe, its AT-content, and reaction conditions.…”
Section: Detection Of Polymorphisms: Hybridizationmentioning
confidence: 99%
“…We took advantage of this fact by developing an algorithm to equalize apparent dissociation temperatures of AT-rich and GCrich duplexes. The former probes are loaded at higher concentration than the latter, facilitating the discrimination on the same chip in similar hybridization conditions [Livshits and Mirzabekov, 1996]. Fotin et al [1998] compared the thermodynamics of duplexes in gel and in solution and found that, although they were qualitatively similar, melting temperatures of the same duplexes in gel were almost 20°C lower than in solution.…”
mentioning
confidence: 99%